Medical negligence: a legal perspective - P S Ranjan, (Fakulti Undang - Undang, 2002)

(untitled)
Usually, medical negligence would lead to a claim for contract. Sometimes, it may amount to a crime or anact of infamous conduct under the Medical Act 1971. Causation is particularly important in medical negligence because often patients have pre-existing or co-existing ailments or injuries when the consult doctors. It is sufficient to establish liability by showing that the breach of duty materially contributed to the injury. Doctors do not undertake to produce desired result. Their duty is to exercise reasonable care and sill in seeking to produce a desired result. Occasionally, a doctor or hospital may be liable for a defective product than for negligence service. The standard of care that is applied in Malaysia is that of the ordinary competent doctor, popularly known as the Balam test. However, the test does not apply to administrative or clerical errors where no question of professional judgment is involved. The test requires expert evidence. In practice, it is easier to succeed in a claim for an administrative or clerical error or system error than for an error of professional judgment. The law provides compensation on the basis of fault, no need, thereby excluding many from compensation